(untitled) (International Journal on Stereo & Immersive Media, 2025)
Today one could argue that cinema has reached a point of ‘technical perfection’, certainly the closest that we have been to what Bazin denominated “total cinema”. Film art has constantly evolved in parallel to technological developments, which have gradually moved forward towards the ‘achievement’ of such a total cinematic experience. In terms of audio, the cinema is today able to absorb us with sounds that emanate from around and above the audience, creating this way highly realistic—although imaginary—three-dimensional worlds. Under this premise, this article aims to explore the technical characteristics of Dolby Atmos, an object-based sound system that has consolidated its position as the leading solution for the production and delivery of immersive cinematic sound. The potential and challenges that this platform presents will be analysed here considering the opinions of several sound professionals, which shall give us clues regarding a better utilization of Dolby’s most advanced sonic platform.